Semiotic Analysis of The Meaning of Protective Instincts on the Lyrics of the Song "Nina" by Feast - Salsabila, Salwa; Baihaqy, Ahnaf; Wulandari, Sri; Andriany, Dian (Jurnal Syntax Transformation, 2025)
Music, as a communicative medium, often conveys profound emotional and social messages. Feast’s "Nina" (2024), a viral Indonesian rock ballad, resonates widely but lacks scholarly analysis of its themes of protective instincts and familial sacrifice. This study deciphers the song’s layered meanings using Roland Barthes’ semiotics (denotation, connotation, myth) and explores how listeners interpret its lyrics. A qualitative-descriptive approach was employed, combining document analysis of lyrics, interviews with teenagers (aged 11–24), and triangulation to validate findings. The denotation depicts a father’s physical and emotional labor; the connotation reveals hope and sacrifice, while the myth aligns with Daedalus-Icarus, symbolizing guidance and life’s struggles. Audience interpretations varied, viewing the song as parental love, sibling bonds, or self-motivation. The study enriches semiotic applications in music analysis and highlights cultural subjectivity in decoding lyrics. Future research could compare cross-generational or cross-cultural interpretations of similar themes.